2019
DOI: 10.17992/lbl.2019.12.262
|View full text |Cite
|
Sign up to set email alerts
|

Blæðingar frá meltingarvegi í íslensku og erlendu samhengi - yfirlitsgrein

Abstract: Blaeðingar frá meltingarvegi eru algeng orsök innlagnar á spítala, nýgengi blaeðinga frá efri hluta meltingarvegar var á árinu 2010 í framskyggnri rannsókn á Íslandi 87/100.000 íbúa 1 og nýgengið var hið sama hvað varðar blaeðingu frá neðri hluta meltingarvegar. 2 Erlendis hefur nýgengi blaeðinga frá efri hluta meltingarvegar verið talið um 90-110/100.000 íbúa/ár í nýlegum framskyggnum rannsóknum, 3-5 en minna í þeim fáu og eldri rannsóknum sem kannað hafa nýgengi blaeðinga frá neðri hluta meltingarvegar, eða … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The crisis caused unprecedented civil and political unrest, and Iceland is still dealing with the aftermath (see, for example, Bernburg, 2016; Johnsen, 2014; Jónsson, 2009; Jónsson and Sigurgeirsson, 2017). The Parliament set up a Special Investigation Commission (SIC) to investigate the causes of the collapse and, in a report, criticized the Icelandic media for its performance in the years leading up to the financial crisis (Hreinsson et al, 2010). The Journalist Union established its own committee to review the SIC report and concluded that the critique was, in many ways, well deserved.…”
Section: The Financial Crisis and The Icelandic News Mediamentioning
confidence: 99%
“…The crisis caused unprecedented civil and political unrest, and Iceland is still dealing with the aftermath (see, for example, Bernburg, 2016; Johnsen, 2014; Jónsson, 2009; Jónsson and Sigurgeirsson, 2017). The Parliament set up a Special Investigation Commission (SIC) to investigate the causes of the collapse and, in a report, criticized the Icelandic media for its performance in the years leading up to the financial crisis (Hreinsson et al, 2010). The Journalist Union established its own committee to review the SIC report and concluded that the critique was, in many ways, well deserved.…”
Section: The Financial Crisis and The Icelandic News Mediamentioning
confidence: 99%